Pengaruh Teknik Relaksasi Front Effleurage terhadap Nyeri Dismenore - Hartati Hartati; Walin Walin; Esti Dwi Widayanti (Jurnal Riset Kesehatan, 2015)
The aim of this research is to determine the effect of relaxation techniques Front Effleurage in reducing pain level of dysmenorrheal. The research design was quasi experimental with pre-post test control group design. The number of sample was 42 and selected by Simple Random Sampling method. The samples were divided into two groups each group of 21 respondents for treatment and control groups. Data were analyzed by paired and independent t-test. The result showed that there was significant difference of pain level between treatment and the control groups with p=0.000 lower than α = 0.005. In conclusion, it can be drawn that Front effleurage method can reduce pain intensity of dysmenorrhea.